Global prevalence of elevated estimated pulmonary artery systolic pressure in clinically stable children and adults with sickle cell disease: A systematic review and meta-analysis - Mobin Ghazaiean; Hadi Darvishi-Khezri; Behnam Najafi; Hossein Karami; Mehrnoush Kosaryan (PLoS ONE, 2025)
Background The current study sought to determine the prevalence of elevated estimated pulmonary artery systolic pressure (ePASP) in clinically stable children and adults with sickle cell disease)SCD(worldwide. Methods The studies included were identified through a search of databases such as PubMed, Scopus, Science Direct, Web of Science, and Embase, as well as Google Scholar engine, adhering to specific inclusion and exclusion criteria. Heterogeneity among the primary study results was assessed using the I-squared index, while publication bias was evaluated through funnel plots, Egger’s test, and trim and fill analysis. All statistical analyses were conducted using R software, version 4.3.0. Results 79 primary studies were included, comprising 6,256 children (<18 years old) and 6,582 adults (≥18 years old) with SCD from 22 countries. The prevalence of elevated ePASP was found to be 21.8% (95% confidence interval [CI]: 18.46 to 25.07) in children and 30.6% (95% CI: 27.1 to 34.1) in adults. The prevalence of elevated ePASP among studies with severe SCD genotypes including HbSS and HbS/β0 was found to be 19.45% (95% CI: 14.95 to 23.95) in children and 29.55% (95% CI: 24.21 to 34.89) in adults. Furthermore, sex-specific prevalence among SCD patients with elevated ePASP indicated the highest prevalence in male children at 60.35% (95% CI: 54.82 to 65.88) and adult female patients at 54.41% (95% CI: 47.3 to 61.5). A comparative analysis of the mean values of clinical and laboratory results revealed significant differences in several characteristics, including age, oxygen saturation, hemoglobin levels, fetal hemoglobin, white blood cell counts, platelet counts, and reticulocyte counts between patients with elevated ePASP and those without, in both children and adult SCD populations. Conclusion Our findings regarding clinically stable SCD patients highlight a high prevalence of elevated ePASP.